Pengaruh Gaya Kepemimpinan, Etos Kerja, Disiplin dan Motivasi terhadap Kinerja serta dampaknya pada Prestasi Kerja Pegawai pada Kantor Kementerian Agama Kota Pangkalpinang - Rissa Mulia Artha; Afrizal Afrizal; Hamdan Hamdan (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to analyze the influence of leadership style, work ethic, discipline, and motivation on performance and its impact on employee performance at the Ministry of Religion Office of Pangkalpinang City, testing the hypothesis by referring to the relationship between three variables, namely independent, intervening and dependent. Sampling using the census method with a population of 63 respondents. The analysis technique to test the hypothesis using multiple linear regression analysis, from the calculation of the correlation analysis, it is found that the relationship between leadership, work culture, motivation to work discipline has a strong relationship between the three. The results of statistical testing show the F test (Simultaneous Test) for the variable Leadership Style, Work Ethic, Discipline, and Motivation has a positive influence on performance. Meanwhile, from the results of the t-test (Partial Test), the variable Leadership Style, Work Ethic, Discipline, and motivation individually (partially) have a significant positive effect on performance. Further research, should add other variables that can affect employee performance, because the better the performance of the employee, it will also have a good effect on the organization.